2003
DOI: 10.1046/j.1365-2222.2003.01731.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the interleukin‐4 and interleukin‐4 receptor α chain genes confer susceptibility to asthma and atopy in a Caucasian population

Abstract: Our data suggest that polymorphisms in the IL-4 and IL-4Ralpha chain genes might play a role both conferring susceptibility to and modulating severity of atopy and asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
77
4
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(91 citation statements)
references
References 30 publications
7
77
4
3
Order By: Relevance
“…[6][7][8][9][10][11] Screening of this SNP in 869 MS patients and 595 controls demonstrated this sequence variation to be associated with MS (see Table 1). Genotyping of two flanking SNPs (rs2243248 and rs2070874) revealed that exclusively the À589 C allele is associated with MS (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11] Screening of this SNP in 869 MS patients and 595 controls demonstrated this sequence variation to be associated with MS (see Table 1). Genotyping of two flanking SNPs (rs2243248 and rs2070874) revealed that exclusively the À589 C allele is associated with MS (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…4 Usually, IL4 is secreted by lymphocytes of the Th2 lineage, 5 whereas the IL4 locus appears silenced in Th1 cells. Because of its immune response regulating role, IL4 is an obvious candidate gene for potential association in MS. We focus here on the IL4 promoter polymorphism À589C/T, since numerous studies have shown association of this single nucleotide polymorphism (SNP) with various inflammatory diseases, including asthma, atopy, brucellosis and rheumatoid arthritis, [6][7][8][9][10][11] and because earlier deletion expression assays hinted to a functional role of this SNP. 12 Genotyping two neighbouring polymorphisms revealed that exclusively SNP À589 C/T is associated significantly with MS.…”
Section: Introductionmentioning
confidence: 99%
“…La région 5q31 a également été associée à l'HRB (Postma et al, 1995;Doull et al, 1996), à Féosinophilie (Martinez et al, 1998) populations caucasiennes (Australie, Canada, Etats-Unis) ont également montré que l'aîlèle IL4*-589T est associé à la respiration sifflante (Walley et Cookson, 1996), à l'asthme, à l'atopie (Zhu et al, 2000) et à de faibles valeurs de VEMS (volume expiratoire maximal en une seconde) chez des sujets asthmatiques (Burchard et al, 1999). Bref, ces données et plusieurs autres suggèrent que le polymorphisme IL4C-589T influencerait la sévérité de l'asthme (Rosenwasser et al, 1995;Suzuki et al, 2000;Beghe et al, 2003), c'est pourquoi il a été sélectionné pour la présente étude.…”
Section: Legèneil4unclassified
“…Parmi eux, quelquesuns ont été associés à l'asthme et à l'atopie (Izuhara et Shirakawa, 1999;Shirakawa et al, 2000;Beghe et al, 2003) et huit sont codants et décrits comme résultant en un changement de conformation de la protéine mature (Deichmann et al, 1997;Hershey et al, 1997;Shirakawa et al, 2000). Ces altérations structurales dans la région extracellulaire du IL- …”
Section: Legèneïl4raunclassified
“…IL-4 is produced by activated T cells, mast cells, and basophils, which participate in IgE synthesis and Th2 phenotype differentiation in T cells, and play a crucial role in the development of atopic diseases including asthma (Beghe et al, 2003).…”
Section: Introductionmentioning
confidence: 99%